Fisiologia da floração e atividade alelopática de Artemisia annua L. cultivar Artemis cultivada em clima subtropical úmido - Magiero, Emanuelle Cavazini (2009)
The Artemisia annua L. (Asteraceae) is a herbaceous plant, native of Asia and acclimated in Brazil. The leaves are abundant source of artemisinin, a sesquiterpene lactone that, jointly to yours derived semi-synthetic, they present effectiveness action against the resistant stumps of the species of Plasmodium against malaria. The artemisinin is also being tested with success in the cancer treatment and against countless parasites that affect the human and animal health. The objectives of this work went to determine the planting times and crop of the cultivar Artemis of A. annua in Pato Branco-PR, as well as, to determine in field the critical photoperiod and the number of inductive photoperiod for the flowering of this cultivar. A second experiment was accomplished with the objective of determining the allellopathic effect of this species on lettuce seeds and wild poinsettia. In the experiment in field, the treatments were six different transplant times, being the 09 central plants of the portions picked for the determination of the mass dries of leaf and stems, relationship leaf/stems and artemisinin in the mass dries of leaves when 50% of the plants of the portion began the emission of the floral buttons. The number of cycles inductive found for the cultivar Artemis was of approximately 36 cycles and the critical photoperiod was approximately 13 hours, that happened in 09/02/2007 in Pato Branco-PR. This results determines that the crop time for cultivar Artemis, in Pato Branco-PR will be in the second fortnight of the month of March. The largest biomass income in that experiment happened in the planting of 27/07/2007, 231 days after the transplant, but it is recommended to take care with the frost that can happen until the first fortnight of September, suggesting choose for the transplant in the second fortnight of September, period free from frost in the area. The largest artemisinin tenor (0,88% in dry matter leaves) was obtained in the times that more they vegetated to field due to the largest biomass production. Besides this experiment, a second experiment was developed to determine the allellopathic effects of this species on lettuce seeds and wild poinsetia. The aqueous extract was prepared starting from fresh leaves in the proportion of 1 L of water distilled for 250 g of the material, after, the extract was filtrate and centrifuged, being used the sobrenadante. The following concentrations of the extract were used: 100%, 75%, 50%, 25% and 0% (distilled water). They were analyzed the variables germinability, germination velocity, germination time, length of the radicle and weight of the dry matter of the seedlings. Aqueous extracts of A. annua is allellopathic on the germination and development of lettuce and wild poinsettia seedlings.